Gaya Komunikasi Politik Twitter Partai Gerindra - Ayu Nenden Assyfa Putri (UNIVERSITAS SARI MUTIARA INDONESIA, 2021)
Social media, especially Twitter, as one of the most widely used platforms on the internet, is now being used by political organizations to convey their political communication messages. This study uses a descriptive qualitative method by analyzing the communication style conveyed by the Gerindra party Twitter account to its followers. In looking for references, researchers use a systematic review method wherein the authors must describe the search to be used, determine where and when they should search, and what terms they should use. The results of this study indicate that the style of political communication conveyed by the Gerindra Twitter account has the aim of being accepted by Twitter users, whose users are young people. Unlike the political communication messages conveyed during the 2014 & 2019 elections, the Gerindra Twitter account conveys its political communication style in a relaxed and informative way. The relevance of the information diffusion theory in this study is when the Gerindra party takes advantage of the great opportunity of Twitter as a social media to communicate its political campaigns so that new voters can accept it in the future.